Urgensi Pemilu Presiden dan Wakil Presiden Secara Langsung di Era Reformasi - Abu Tamrin (Jurnal Cita Hukum, 2013)
Abstract: the Importance of Direct Presidential and Vice Presidential Election in Reformation Era. Direct president and vice president election has begun in 2004 based on Act Number 23 Year 2003and renewed by Act Number 42 Year 2008. The importance of this provision is that elected president and vice president reflect the choice of majority of people. Beside of preventing problems in Parliament, this provision is also aimed to keep the sustainability of President both as head of government and head of State So,  it would not be easy for him to be removed or impeached. DOI: 10.15408/jch.v1i2.2990